Parametric Optimization and Control of Heat Exchanger using Linear Quadratic Controller and Dynamic Matrix Controller - Kesavan, E; Divya, N; Gowthaman, N; Manoharan, S (International Journal of Engineering and Technology, 2018)
Heat exchanger plays a important role in many unitsas they have the capability to hold different temperarure and pressure range. In this paper the linear quadratic controller and Dynamic matrix controller is implemented for heat exchanger system. The Â out let temperature of the tube is controlled by monitoring the inlet flow rate by using different controllers. The model of the system has been obtained from experimental data using system identification technique. The LQR and DMC is compared by analyze the servo performance in the system in terms of settling time, overshoot and rise time.Â
Keywords: Heat exchanger system; DMC controller; LQR Controller; Cold water temperature